Analisis Pengaruh Pengalaman Masa Lalu Terhadap Minat Menginap Kembali Di Hotel Era Pandemi Covid-19 Dengan Consumer Review Sebagai Variabel Moderasi - Fatika, Baiq Deria Ayuning; Sulhaini, Sulhaini; Rinuastuti, Baiq Handayani (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study was to determine the effect of past experience on the intention to return to stay at hotels during the Covid-19 pandemic with consumer reviews as a moderating variable. The type of research used is associative quantitative research. The population in this study were all visitors at the Mataram Hotel. According to the sampling technique used, non-probability sampling was used with a convenience sampling approach. Seeing the different number of respondents from previous studies, this research will take 200 respondents, 100 respondents each for non-star hotel guests and star hotel guests. The instrument used in this research is a questionnaire. Data were analyzed using Structural Equation Modeling with the help of the Partial Least Square (PLS) program. The results of the study concluded that past experience had a significant effect on the intention to stay again at Starred and non-Starred Hotels in the Covid-19 Pandemic Era, Accepted. Consumer reviews moderate the significant effect of past experience on the intention to stay again at Starred Hotels in the Covid-19 Pandemic Era Accepted, while the non-Starred Hotel respondents stated that consumer reviews moderated the significant effect between past experiences on the intention to stay again at Hotels in the Covid-19 Pandemic Era. 19 Rejected.